STUDENTS’ ERROR IN USING CAPITAL LETTERS AND PUNCTUATION IN WRITING A DESCRIPTIVE TEXT - Ghina Fikriani Rahman; Deddy Sofyan; Gusnadi Gusnadi (Pedagogia: Jurnal Ilmiah Pendidikan, 2017)
The paper entitled “Students’ Error in Using Capital Letter and Punctuation in Writing a Descriptive Text” was written to find out error in using capital letter and punctuation in writing a descriptive text and the cause of it. The method used in this research is descriptive method. The research was conducted to the third semester students of English Education Study Program, Faculty of Teachers Training and Educational Sciences, Pakuan University. The sample of this research is selected by using purposive sampling technique. The data were collected through students’ work, questionnaire, and interview. The result of the data shows that the most common error in using capital letter is in writing the names of places and persons. For comma, students make error before or after coordinating conjunction and comma at the end of the sentence. For apostrophe, most of students make errors by omitting a letter or letter in contractions. The writer also finds that carelessness is the cause of students’ error in using capital letter and punctuation in writing a descriptive text